(untitled) (Ameghiniana, 2014)
A detailed paleoecologic analysis has been carried out in the Ordovician limestones of the San Juan Formation in the Argentine Precordillera. The sarnples were collected in the middle part of the formation (Early to middle Arenig) at the Niquivil section, in levels of the Archneorthis, Huncoella and Niquivilia brachiopod biozones. Fossil associations were analised along the stratigraphic section in order to recognize communities, their vertical variation and internal structure (richness, diversity, tiering and guild composition). On the basis of biovolumetric and multivariate analysis, including dominant species analysis, several communitiy groups are distinguished: Fisherites-dominated communities (Fisherites-Ranorthis, Fisherites-Archaeoscyphia and Fisllerites- Macluritacean- Nexospongia communities), Macluritacean domina ted cornmunities (Macluritacean- Pentamerid, Macluritacean-Illaenus-Nexospongia, Macluritacean- Illnenus-Nicbotsoneíla and Macluritacean-Allnalllitella-Archaeoscyphia communities), lllaenus-dominated communities (Illaenus-Psarodictyum community), and biologically accommodate communities Ranorthis, Tritoechia-lllaenus-Anruintitelln and lllaellus-Fisherites-Rophalocoelia communities). The results were compared with similar paleoecologic studies developed in younger communities (Llanvirn) of the same unit. Although the ecological structure and tiering of both intervals are very similar, Llanvirn communities are dominated by epífaunal, suspension-feeders. This fact suggests that nutrients and plankton were more abundant in the upper levels of the formation. Lower diversity and varied values in dominance shown by the studied communities reflect minor degree in the exploitation of resources and niche partitioning. Composition and diversity of communities were controlled by gradual changes in depth, while disruption in cornmunity development was influenced by abrupt changes in hydrodynamic regime (storms). Biotic interactions became important in community dynamics in stable environments, when diversity rises. This pattern of highly variable community composition and the absence of recurrent communities may imply the absence of refuge areas, possibly related to the isolation of the Argentine Precordillera.